Policymaking integration, policy coherence, and whole-of-government approaches: a qualitative systematic review of advice for policymakers [version 1; peer review: 1 approved, 2 approved with reservations] - Paul Cairney (Open Research Europe)
Background The pursuit of policymaking integration and policy coherence represents the ultimate gap between aspiration and reality. Policy processes are too fragmented to produce coherent policies to address complex problems. Whole-of-government and joined-up-government are popular buzzwords that struggle for meaning and traction. How can policymakers and researchers address this problem? I searched multiple academic literatures for advice on policy coherence via policymaking integration. Methods A qualitative systematic review of 705 academic journal articles identified in two systematic reviews on ‘whole-of-government and joined-up government’ (WG/JUG, 340) and ‘policy integration’ (PI, 413), and snowballed texts in academic and grey literatures (65) (net total 770). I searched each text for advice on how to foster policymaking integration in the service of policy coherence. I used an immersive inductive approach, and policy theory insights, to identify common themes. Results Most accounts describe aspirations for integration and coherence. Few describe substantive progress. The literature describes requirements for integration and coherence and inevitable or routine policymaking barriers. This comparison of barriers and facilitators helps to inform a realistic approach, to combine managed expectations and practical advice. Conclusions Five themes of practical advice connect aspiration to limited progress. Explain what policymaking integration means, since a rhetorical commitment means nothing. Identify your rationale, model, and theory of change. Engage with trade-offs between top-down and bottom-up conceptions of policy coherence. Explain why the pursuit of integration has advantages over a reasonable alternative, such as specialisation. Learn about facilitators from studies of success and barriers from studies of failure. These lessons help to clarify your aims, connect them to routine government business, and ensure capacity to deliver. If this advice seems obvious, we should reflect on its lack of traction when governments lack the willingness and ability to follow it.